2015
DOI: 10.3390/ma8125445
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Dynamic Effects of FRP Reinforced Masonry Vaults

Abstract: An increasing interest in the preservation of historic structures has produced a need for new methods for reinforcing curved masonry structures, such as arches and vaults. These structures are generally very ancient, have geometries and materials which are poorly defined and have been exposed to long-term historical movements and actions. Consequently, they are often in need of repair or reinforcement. This article presents the results of an experimental study carried out in the laboratory and during on-site t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In the last decade many experimental and numerical studies were performed on masonry arches reinforced with FRP materials. Several studies [3]- [6], demonstrated the efficiency of this reinforcement technique, both in terms of the maximum load applied and of displacement at collapse. In some cases the application of a continuous FRP textile prevented the formation of the typical hinge-based failure mode and the collapse was caused by debonding of the FRP.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the last decade many experimental and numerical studies were performed on masonry arches reinforced with FRP materials. Several studies [3]- [6], demonstrated the efficiency of this reinforcement technique, both in terms of the maximum load applied and of displacement at collapse. In some cases the application of a continuous FRP textile prevented the formation of the typical hinge-based failure mode and the collapse was caused by debonding of the FRP.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Traditional techniques of strengthening (steel bars, stirrups, steel profiles, injecting cementitious mortar, reinforced concrete hoods, and introducing ties at the arch impost) are being abandoned due to the aesthetic incompatibility and extra self-weight and rigidity that these techniques could add to the structure [36]. Recently, composite materials have been used instead of traditional techniques, because they are considered innovative (carbon fiber reinforced polymer, glass reinforced polymer, steel rod, steel-reinforced grout, basalt textile-reinforced mortar, or other fiber materials) [37][38][39][40][41][42]. An interesting way of reinforcing a masonry arch railway bridge was recently presented [43].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the probabilistic nature of earthquakes, directly connected and influenced by a large number of parameters, must be taken into account. Due to the high uncertainty of the parameters influencing the behavior of masonry structures, the assessment of their vulnerability cannot be conducted in terms of a deterministic approach [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. To the contrary, a probabilistic approach would be more appropriate, in order to be applied in cases where the response of the structure is evaluated and compared with limit states, such as specific limit values of response directly interlinked with structural damages.…”
Section: Introductionmentioning
confidence: 99%